Strategi Active Learning dalam Pembelajaran Akidah Akhlak: Prinsip dan Urgensi Penerapannya di Madrasah Ibtidaiyah - Danuwara, Prima; Maghribi, Hamdan (Tarbiyatuna: Jurnal Pendidikan Ilmiah, 2023)
Madrasah Ibtidaiyah (MI) is a basic/primary education level where at this level, learning should begin to teach students to think actively, creatively, critically, so that they are trained from an early age to apply learning outcomes in their daily lives. Especially in the Aqidah Akhlak lesson, where the direction of achievement of this learning is not just understanding theories in terms of faith and behavior, but until students can apply good behavior as a habit that they carry out every day. Teachers of moral beliefs at the MI level need guidance on how to apply an active learning strategy or method so that learning objectives can be achieved successfully. The aim of this research is to present a discussion about the principles and urgency of implementing active learning strategies in learning moral beliefs for students at the MI level. The research method is library-research, where research data is taken from books and scientific articles from the internet that are relevant to the research discussion. The research results show that learning moral beliefs using an active learning strategy aims to make students more active, interesting and encouraging to attract interest in learning. Active learning can use the basic principles of speaking and listening, reading, writing and reflection methods on students. This strategy is urgent to implement because it can encourage students to become creative individuals in contextualizing the material they receive with their surroundings. In the context of learning moral beliefs, it will provide experience for students so that they are ready to face and answer problems that arise in an era that continues to develop by becoming polite, civilized, moral individuals who have faith and devotion to Allah SWT.